Assistance to Farmers in Increasing Rice Production Through Direct Seed Planting System in Langsat Permai Village, Bungaraya District - -, Hapsoh (Journal of Saintech Transfer, 2023)
The increase in agricultural yields of food crops and horticulture in Langsat Permai Village, Bungaraya District was initiated by the construction of canal blocking in the activities of the Partner Village Service Program by DIKTI in the 2017-2019 implementation year which will continue until 2023. However, the harvest index (HI) of rice has not reached 300 due to the transplanting system, so that it takes quite a long time from the transplanting period to finally harvesting and replanting. Therefore, the rice cultivation system with the direct seed planting system can be a solution that can help farmers increase the harvest index (HI) and rice crop production. The activity partners who were the targets of the activity were farmers and members of the Langsat Permai Village youth group. Assistance is carried out by providing knowledge about rice cultivation using the direct seed planting system starting from the understanding of the direct seed planting system, its tool, the advantages and disadvantages of rice cultivation using the direct seed planting system, as well as the stages of the direct seed planting system cultivation from land preparation, seed preparation, planting to fertilization. Based on the results of the mentoring carried out, the knowledge of farmers and youth groups in Langsat Permai Village about rice cultivation using the direct seed planting system has increased compared to before the mentoring activities were carried out.